Endoscopic retreatment of recurrent choledocholithiasis after sphincterotomy. Issue 12 (11th November 2004) - Sugiyama, M; Suzuki, Y; Abe, N; Masaki, T; Mori, T; Atomi, Y
Abstract : Background: Endoscopic sphincterotomy (ES) carries a substantial risk of recurrent choledocholithiasis but retreatment with endoscopic retrograde cholangiopancreatography (ERCP) is safe and feasible. However, long term results of repeat ERCP and risk factors for late complications are largely unknown. Aims: To investigate the long term outcome of repeat ERCP for recurrent bile duct stones after ES and to identify risk factors predicting late choledochal complications. Methods: Eighty four patients underwent repeat ERCP, combined with ES in 69, for post-ES recurrent choledocholithiasis. Long term outcomes of repeat ERCP were retrospectively investigated and factors predicting late complications were assessed by multivariate analysis. Results: Complete stone clearance was achieved in all patients. Forty nine patients had no visible evidence of prior sphincterotomy. Two patients experienced early complications. During a follow up period of 2.2–26.0 years (median 10.9 years), 31 patients (37%) developed late complications, including stone recurrence (n = 26), acute acalculous cholangitis(n = 4), and acute cholecystitis (n = 1). There were neither biliary malignancies nor deaths attributable to biliary disease. Multivariate analysis identified three independent risk factors for choledochal complications: interval between initial ES and repeat ERCP ⩽5 years, bile duct diameter ⩾15 mm, and periampullary diverticulum. Choledochal complications were successfully treated with repeat ERCP in 29 patients. Conclusions: Choledochal complications after repeat ERCP are relatively frequent but are endoscopically manageable. Careful follow up is necessary, particularly for patients with a dilated bile duct, periampullary diverticulum, or early recurrence. Repeat ERCP is a reasonable treatment even for recurrent choledocholithiasis after ES.